2002
DOI: 10.1002/mc.10013
|View full text |Cite
|
Sign up to set email alerts
|

Protease inhibitor–induced stabilization of p21waf1/cip1 and cell‐cycle arrest in chemical carcinogen–exposed mammary and lung cells†

Abstract: In previous studies, we have shown that human breast and lung carcinoma cells and mouse nontransformed type II lung cells fail to undergo cell-cycle arrest in G(1) phase in response to treatment with hydrocarbon carcinogens but rather accumulate in the S phase with damaged DNA. This situation may lead to replication of DNA on a damaged template and enhance frequency of mutations. The mechanism of this G(1) arrest failure was examined. Western immunoblot analyses of MCF7 human mammary cancer cells exposed to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
3
3
0
Order By: Relevance
“…2A). The inability of BaP treatment to affect p21 WAF1 expression was not unexpected, since studies published elsewhere have reported that bypassing p21 WAF1 tumor suppressor functions is a characteristic of the stealth nature of cigarette smoke carcinogens, by which the carcinogens induce DNA damage and propagate mutations without inducing cell cycle arrest (20,35,36). However, in the current study, the observed lack of p21 WAF1 induction with BaP could also be due to the HPV E6 oncoprotein targeting of p53 functions.…”
Section: Resultssupporting
confidence: 52%
“…2A). The inability of BaP treatment to affect p21 WAF1 expression was not unexpected, since studies published elsewhere have reported that bypassing p21 WAF1 tumor suppressor functions is a characteristic of the stealth nature of cigarette smoke carcinogens, by which the carcinogens induce DNA damage and propagate mutations without inducing cell cycle arrest (20,35,36). However, in the current study, the observed lack of p21 WAF1 induction with BaP could also be due to the HPV E6 oncoprotein targeting of p53 functions.…”
Section: Resultssupporting
confidence: 52%
“…p27 transcription and degradation, in turn, was also shown to be mediated by calpains in other models, including osteoblasts, cortical neurons and preadipocytes [51][53]. Further, p21 accumulation induced by calpain inhibition has also been observed in other studies, where in vitro incubation with calpain 1 and 2 resulted in rapid degradation of p21 [54],[55]. It has been demonstrated that calcium oscillations occurring in G1 to S transition are required for cell cycle progression in both neural progenitor and undifferentiated cells, correlating with G1 shortening and increased proliferation [22], [56].…”
Section: Discussionsupporting
confidence: 53%
“…Cip1 is a calpain substrate in cytomegalovirus-infected and chemical carcinogen-exposed lung and mammary cells (6,20); however, we detected slight, if any, accumulation of p21…”
Section: Discussionmentioning
confidence: 59%